Matharpacady-18.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Despite its proximity to the sea, Mazagaon had an abundant freshwater supply. Wells were the only sources of drinking water before tap water was made available inside homes. This is the central well of Matharpacady, located in a circle known as Brahmin Chawl. This was the only source of fresh water in the past but is no longer used and remains covered up. Other than this public well, there were also private wells inside houses.